Effects of neuroticism on suicide risk in major depressive disorder and bipolar disorder - Xing, Yujie; Li, Tian; Mao, Zhen; Zhao, Lei; Sun, Yue; Jiang, Qitong; Wang, Chuanyue; Bo, Qijing (Frontiers in Psychiatry, 2025)
BackgroundSuicide is the primary cause of death in patients with major depressive disorder (MDD) or bipolar disorder (BD). Among various personality traits, neuroticism is particularly relevant to suicide risk. However, its role in MDD and BD has not been examined sufficiently. This study characterized neuroticism in patients with MDD or BD, and analyzed the association between neuroticism and suicide risk in these patients.MethodsThis study collected demographic information and personality traits of MDD and BD patients. Group differences were assessed using t-tests, chi-square tests, and Mann-Whitney U tests. To identify factors associated with suicide risk, correlation analysis was first conducted, followed by bivariate and generalized ordered logistic regression for significant variables, including neuroticism. Sensitivity analyses were performed by progressively excluding potential confounders to evaluate the robustness of neuroticism’s effect. Additionally, simple mediation analyses using a bootstrap approach were conducted to examine whether depressive symptoms mediated the association between neuroticism and suicide risk in MDD and BD separately. A two-tailed P < 0.05 was considered statistically significant.ResultsThe study population comprised 88 MDD patients and 90 BD patients. Lifetime suicide risk was present in 39.3% of the study population. In the entire sample, neuroticism was significantly associated with both lifetime (r = 0.18, P = 0.018) and current suicide risk (r = 0.17, P = 0.024). In patients with MDD, through mediation analysis, neuroticism predicted both depressive symptom severity (B = 0.25, P < 0.001) and current suicide risk (B = 0.02, P = 0.022), while also indirectly influencing current suicide risk through depressive symptoms (B = 0.01, 95% CI = 0.01–0.02). In BD patients, neuroticism predicted depressive symptoms (B = 0.13, P = 0.002) but not current suicide risk (B < 0.01, P = 0.714), while depressive symptoms fully mediated this relationship (B = 0.06, P < 0.001).ConclusionNeuroticism plays a significant role in influencing suicide risk among MDD and BD, through its effect on depressive symptoms. Interventions for neuroticism can reduce depressive symptoms and suicide risk. This highlights the necessity of identification and management of neuroticism in suicide prevention strategies.